Morfometria e anatomia de arcídeos (Mollusca, bivalvia) da costa Norte-Nordeste do Brasil - Rocha, Valesca Paula (2011)
Aiming to supplement conchology literature information on the family Arcidae was used morphometric approach - which allows comparison of morphological patterns from multivariate character while considering various characteristics in a complex body structure. The specimens available for study are from the malacological collection "Prof. Henry Ramos Matthews (CMPHRM), Federal University of Ceará (UFC), where the right valves were used. After identification, using calipers, were taken eight measures: length of the trough, shell length, position of beak (prodisoconcha), beak height, height of the anterior portion of the shell, the shell height, height of the posterior portion of the shell and length of the posterior portion of the shell. The measures are previously known as 'landmarks' of the family. Then the data were analyzed by statistical packages. The mean sizes of the shells of our specimens had to be consistent measures presented in the literature. Prodisoconcha of morphometric data were not as significant in the differentiation of species. With the data obtained in this study, morphometric analysis of the species formed a heterogeneous graph similarity. The different populations that have geographical proximity, have morphological similarity.